2022
DOI: 10.3390/tropicalmed7040052
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antiretroviral Therapy by Medication Possession Ratio and Virological Suppression among Adolescents and Young Adults Living with HIV in Dar es Salaam, Tanzania

Abstract: Background: Adherence to antiretroviral therapy (ART) is a strong determinant of virological suppression. We aimed to determine the magnitude of adherence as measured by medication possession ratio (MPR) and virological suppression with its predictors among adolescents and young adults (AYA) living with HIV on ART in Tanzania. Methods: This retrospective cohort study was conducted using archived data from HIV care and treatment centers in Dar es Salaam, Tanzania between 2015 and 2019. The logistic regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
8
0
3
Order By: Relevance
“…This approach also secured organizational backing, addressing a common barrier in mHealth implementation [37,42] . These issues necessitated supplementary documentation methods, raising questions about the app's practicality and, thus, the usefulness of the app, even if they recognize its theoretical benefits [43,44]. Technological challenges, which are common barriers to implementing and adopting mHealth interventions [40,45,46] were among the factors contributing to the delays in addressing CARES issues.…”
Section: Discussionmentioning
confidence: 99%
“…This approach also secured organizational backing, addressing a common barrier in mHealth implementation [37,42] . These issues necessitated supplementary documentation methods, raising questions about the app's practicality and, thus, the usefulness of the app, even if they recognize its theoretical benefits [43,44]. Technological challenges, which are common barriers to implementing and adopting mHealth interventions [40,45,46] were among the factors contributing to the delays in addressing CARES issues.…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating the findings, a study carried out in Uganda with adolescents and young people living with HIV, selected in specialized clinics, showed that care transition generally occurs between 22 and 24 years of age, as cognitive, sexual, psychological and physical maturity can influence this process ( 18 ) . A retrospective cohort study, carried out with adolescents and young people in Tanzania, also identified that being aged between 20 and 24 years old was associated with reduced adherence, showing that one out of three young individuals abandon ART ( 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Un estudio retrospectivo de cohortes de adolescentes y jóvenes en Tanzania también descubrió que tener entre 20 y 24 años estaba asociado a una menor adherencia, mostrando que uno de cada tres jóvenes abandona la terapia antirretroviral (19) .…”
Section: Abandonounclassified